Ocular hypertension in pediatrics patients with acute lymphoblastic leukemia (Research, Society and Development, 2022)
Objectives: To evaluate the frequency and associated factors with ocular hypertension (OH) in patients with acute lymphoblastic leukemia (ALL) using glucocorticoids (GC), in order to determine intraocular pressure (IOP) at four times along the treatment (first day – D0, after eight days – D8, after twenty-eight days – D28 and after 6 months – D6m) and to identify association of OH with IOP, age group, cerebrospinal fluid (CSF) infiltration, immunophenotyping (IMP), sex and death. Methodology: Prospective descriptive study design enrolling children with ALL under chemotherapy at a public and specialized in pediatric oncology ward from January/2013 until December/2017. IOP was measured on D0, D8, D28 and D6m of treatment. Measurements above 21 mmHg were considered HO. Results: Of the 58 patients included (aged between 1.4 and 19.2 years), 17.2% (10 patients) had OH, with higher blood pressure increases on D8 (p